Antecedents of the Internationalization and the Relationship between Internationalization and Performance of Malaysian Small and Medium Manufacturing Enterprises (SMEs) - Chelliah, Shankar (2004)
Despite the importance of SMEs and the increased in knowledge in the area of internationalization, empirical research on Malaysian SMEs in the area of internationalization has been limited. In an attempt to investigate the antecedents of internationalization that influence the performance of SMEs, this study focuses on SMEs in the Malaysian manufacturing sector. The conceptual framework is developed based on previous literature gaps on SME internationalization and firm performance.